2005
DOI: 10.1590/s1516-89132005000300013
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Chirocentrodon bleekerianus (Poey, 1867) (Clupeiformes: Pristigasteridae) in a continental shelf region of southern Brazil

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
1
8
0
2
Order By: Relevance
“…Like other species, females tend to be more abundant that males in Clupeiformes (Tsikliras and Koutrakis, 2013). Studies in other environments have also shown a strong female bias in various Clupeiformes species (Fialho et al, 2000;Corrêa et al, 2005;Deshmukh et al, 2010). This bias could be explained by ecological factors (Gamble and Zarkower, 2012), environmental conditions, reproductive behavior, or food availability (Vandeputte et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Like other species, females tend to be more abundant that males in Clupeiformes (Tsikliras and Koutrakis, 2013). Studies in other environments have also shown a strong female bias in various Clupeiformes species (Fialho et al, 2000;Corrêa et al, 2005;Deshmukh et al, 2010). This bias could be explained by ecological factors (Gamble and Zarkower, 2012), environmental conditions, reproductive behavior, or food availability (Vandeputte et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…It is a characteristic species of coastal areas (CarvalhoFilho 1999), but there are only two previous records for the coast of Pernambuco (Lira & Teixeira 2008). Adults might reach the surf zone in search for food, as they eat some fish and crustaceans (Corrêa et al 2005), preys commonly found in this ecosystem. The time of higher incidence of C. bleekerianus coincided with the peak of juvenile Engraulidae and post-larvae of penaeid shrimp (personal observation) in this season (July-October).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that first order carnivores had shown high density at night is mainly associated with L. breviceps and C. spixii, which were the most abundant species during this period. C. bleekerianus is a piscivore or third order carnivore as adult, feeding mainly on small fish (Sazima et al, 2004;Corrêa et al, 2005). Based on the length of first sexual maturity (76 mm) (Corrêa et al, 2005), 90% of C. bleekerianus sampled was composed of adults.…”
Section: Discussionmentioning
confidence: 99%
“…C. bleekerianus is a piscivore or third order carnivore as adult, feeding mainly on small fish (Sazima et al, 2004;Corrêa et al, 2005). Based on the length of first sexual maturity (76 mm) (Corrêa et al, 2005), 90% of C. bleekerianus sampled was composed of adults. This fact demonstrates the availability of small fish in the sampling area.…”
Section: Discussionmentioning
confidence: 99%